Obstetric outcomes of grand multiparous women in Soweto - Bhoora, Shastra (My University, 2015)
Background Grand multiparous women, defined as women who have had five or more deliveries, have historically been considered to be at risk for maternal and fetal complications. Over the years, these complications have been attributed to physiological changes as a result of high parity, maternal age, age-related medical conditions and socioeconomic status. Recent research has indicated a strong relationship between access to health care, especially in the antenatal phase, and outcomes. This work aimed to describe maternal, obstetric and fetal complications occurring in GM women, to determine their attendance at antenatal clinic, to review their modes of delivery and to identify any demographic characteristics related to GMP. Methods This was a prospective, descriptive study undertaken at Chris Hani Baragwanath Academic Hospital, a tertiary and regional hospital situated in Soweto that serves approximately two million people within its jurisdiction. In excess of 23 000 deliveries take place there each year. The labour ward attends mostly to high-risk women and approximately 20 % low-risk walk-ins. Another 10 000 births are conducted at midwife obstetric units in Soweto. This study surveyed a sample of pregnant women presenting at Chris Hani Baragwanath and the referring midwife obstetric units who had had five or more viable deliveries, including the current birth, and was conducted over four months in 2011. Results A total of 122 women were included with 124 deliveries as there were two twin pregnancies. Detailed data were available for 98 of these women. The study group were largely of advanced maternal age and were generally healthy. The attendance rate at antenatal care was high (91.35%). Antepartum and postpartum complications were infrequent and there were no intensive care unit admissions or maternal deaths. The CS rate was high (32.79 %), with more emergency CSs performed than elective CSs. The majority of the emergency CSs performed was as a result of fetal distress. There were four stillbirths (3.23%), and 25 (20.16%) of infants weighed <2500g at birth. Conclusion This study showed good maternal and fetal outcomes in a group of GM women who have access to and who largely attended antenatal care facilities. The results, albeit from a small sample, do not support traditional views that GM women are at risk of poor outcomes due to advanced maternal age, physiological changes as a result of high parity or low socioeconomic status. GM women who are generally healthy and are afforded access to adequate health care facilities should have good pregnancy outcomes.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in Obstetrics and Gynaecology MMed (O&G) Johannesburg, October 2014
Keywords: Obstetric Labor Complications